A cross sectional observation study of postmenopausal symptoms and hormonal management - Ambika Patil; Saleha Inamdar; Archana T (Al Ameen Medical College, 2024)
Aim: The aim of this study is to determine the age and symptoms in menopausal women and providing hormonal treatment. Materials and Methods: This study was a community based cross sectional, descriptive, observational study conducted among 400 rural women living in and around Vijayapur. Women aged 40 to 55 years who attained natural menopause and cessation of menses for one year were included in the study. The study was carried out from November 2022 to October 2023. Ethical clearance has been taken for this study. The participants were interviewed on one-to-one basis using a self-constructed semi structured questionnaire. Results: A total of 400 women belonging to the age group of 40 to 55 years participated in the study. The mean age of the participants was 52.01 ± 2.89 years. The mean age of attaining menopause was 45.67 ± 3.9 years. The least age of attaining menopause was 37years and the maximum age noted was 54 years. Most women (55%) attained menopause in the age group of 45 to 49 years. The incidence of premature menopause was 4.6%. In women with hysterectomy Estrogen alone therapy is beneficial and in women with intact uterus, estrogen progesterone therapy is recommended. Conclusion: Almost majority of women are affected by menopausal symptoms and due to sociocultural factors, economic factors adversely affecting the women health. Better to initiate women with hormonal therapy in women with severe symptoms.